Implementasi Program Jangtas Dalam Meningkatkan Mutu Pendidikan - Handayani, Dwi Putri; Juharyanto, Juharyanto; Sunandar, Asep (Proceedings Series of Educational Studies, 2024)
Abstract Improving the quality of education is one of the triggers for a strategy in management to improve the quality and strength of school. Every school must have a desire to compete so as to obtain quality school quality quality that can be seen as good by the wider community. Total Quality Management (TQM) is a management concept that helps an organization to improve quality. In this article, the aim is to finf out school management in improving the quality of education in schools includes: (1) Programs that can improve the quality of schools; (2) Planning programs that can improve the quality of education in schools; (3) Implementation of school programs that can improve school quality management; (4) Evaluation of programs in improving the quality of education in schools. UM Laboratorium Middle School has various excellent programs that bridge schools to high quality educational institutions. One of these programs is the Creativity Event (JANGTAS). In this article using the research method is a qualitative research type where research data is obtained through observation and interviews as well as various other literature as a basis for conducting research. It is hoped that the planned program can improve the quality and qualitu of education in schools. Abstrak Peningkatan mutu pendidikan merupakan salah satu pemicu adanya strategi dalam manajemen untuk meningkatkan kualitas dan kekuatan pada sekolah. Setiap sekolah pasti memiliki keinginan dalam bersaing sehingga memperoleh kualitas mutu sekolah yang dapat dipandang baik oleh masyarakat luas. Total Quality Management (TQM) merupakan konsep manajemen yang membantu dalam sebuah organisasi untuk meningkatkan kualitas. Dalam artikel ini memiliki tujuan dalam mengetahui manajemen sekolah dalam meningkatkan mutu pendidikan yang ada di sekolah meliputi: (1) Program yang dapat meningkatkan mutu sekolah; (2) Perencanaan program yang dapat meningkatkan mutu pendidikan di sekolah; (3) Pelaksanaan program sekolah yang dapat meningkatkan manajemen mutu sekolah; (4) Evaluasi program dalam peningkatan mutu pendidikan di sekolah. SMP Laboratorium UM memiliki berbagai program unggulan yang menjembatani sekolah menuju lembaga pendidikan yang bermutu tinggi. Salah satu program tersebut yaitu Ajang Kreativitas (JANGTAS). Dalam artikel ini menggunakan metode penelitian kualitatif dimana data diperoleh melalui observasi dan wawancara serta berbagai literatur lain sebagai landasan dalam pelaksanaan penelitian. Diharapkan dalam program yang telah direncanakan dapat meningkatkan kualitas serta mutu pendidikan pada sekolah.